ذكر مؤشرات التسيير المالي في تحسين الأداء المالي للمؤسسة الصناعية - دراسة حالة مؤسسة بلغيث الكبرى - هبة الرحمن بشقاوي; أسماء بشقاوي (My University, 2021)
This study aims to know the role of financial management indicators in improving the financial performance of the institution by using the study variables represented in a set of financial indicators, their processing and analysis in order to evaluate the financial performance of the institution. The study included a theoretical aspect and an applied aspect, where we relied on the descriptive approach and the case study approach. And in order to know the field impact of this study, we studied the case of the Grand Balghith Mills Corporation for the period from (2018-2020), where the most important indicators of financial management were extracted, which are indicators of financial balance, profitability indicator, indicators of ability to pay (liquidity), in addition to To the indicators of efficiency in managing assets for the period mentioned in this study. Through this study, we reached a set of results, the most important of which was: The indicators of financial management in general are very important financial indicators in improving the financial position of the institution under study, identifying and treating all deviations and revealing the level of its financial performance and giving a clear picture of enterprise in the market. ............................................... تهدف هذه الدراسة إلى معرفة دور مؤشرات الإدارة المالية في تحسين الأداء المالي للمؤسسة من خلال استخدام متغيرات الدراسة المتمثلة في مجموعة من المؤشرات المالية ومعالجتها وتحليلها بهدف تقييم الأداء المالي للمؤسسة. وتضمنت الدراسة جانباً نظرياً وجانباً تطبيقياً، حيث اعتمدنا على المنهج الوصفي ومنهج دراسة الحالة. ولمعرفة الأثر الميداني لهذه الدراسة قمنا بدراسة حالة شركة مطاحن بلغيث الكبرى للفترة من (2018-2020) حيث تم استخلاص أهم مؤشرات الإدارة المالية وهي مؤشرات التوازن المالي، مؤشر الربحية، مؤشرات القدرة على الدفع (السيولة)، بالإضافة إلى مؤشرات الكفاءة في إدارة الأصول للفترة المذكورة في هذه الدراسة. ومن خلال هذه الدراسة توصلنا إلى مجموعة من النتائج كان أهمها: مؤشرات الإدارة المالية بشكل عام مؤشرات مالية مهمة جداً في تحسين الوضع المالي للمؤسسة محل الدراسة وتحديد ومعالجة كافة الانحرافات والكشف عن مستواها. لأدائها المالي وإعطاء صورة واضحة عن المؤسسة في السوق. .......................................... .Cette étude vise à connaître le rôle des indicateurs de gestion financière dans l'amélioration de la performance financière de l'institution en utilisant les variables d'étude représentées dans un ensemble d'indicateurs financiers, leur traitement et leur analyse afin d'évaluer la performance financière de l'institution. L'étude comprenait un aspect théorique et un aspect appliqué, où nous noussomme sappuyéssur l'approche descriptive et l'approche par étude de cas. Et afin de connaître l'impact terrain de cette étude, nous avons étudié le cas de la Grand Balghith Mills Corporation pour la période de (2018-2020), où les indicateurs les plus importants de gestionfinancièreontétéextraits, qui sont des indicateursd'équilibre financier, indicateur de rentabilité, indicateurs de capacité à payer (liquidité), en plus des indicateursd'efficacitédans la gestion des actifs pour la périodementionnéedanscetteétude. A travers cetteétude, nous avonsatteint un ensemble de résultatsdont le plus important était : Les indicateurs de gestionfinancière en généralsont des indicateurs financiers trèsimportants pour améliorer la situation financière de l'institutionétudiée, identifier et traitertous les écarts et révéler le niveau de ses performances financières et de donnerune image claire de l'entreprisesur le marché.